Pengaruh Beban Kerja, Disiplin Kerja dan Kompensasi Terhadap Kinerja Guru - Sri Hariati Hasibuan; Adi Munasib (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2020)
The purpose of this study was to determine the effect of workload, work discipline, and compensation on teacher performance in private madrasah ibtidaiyah in sub-districts of Rantau Utara District, Labuhanbatu Regency. This type of research is associative. The sampling technique in this study using saturated sampling of 37 teachers. The analysis technique used is multiple regression. The results of this study partially show that workload has a negative and insignificant effect on teacher performance, work discipline has a positive and insignificant effect on teacher performance, compensation has a positive and significant effect on teacher performance in private madrasah ibtidaiyah in sub-districts of Rantau Utara District, Labuhanbatu Regency. Simultaneously workload, work discipline, and compensation have a significant effect on teacher performance in private madrasah ibtidaiyah in sub-districts of Rantau Utara District, Labuhanbatu Regency.